2014
DOI: 10.1038/nsmb.2796
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptionally active chromatin recruits homologous recombination at DNA double-strand breaks

Abstract: While both Homologous recombination (HR) and Non Homologous End Joining (NHEJ) can repair DNA double Strand Breaks (DSB), the mechanisms by which one or other of these pathways is chosen remain unclear. Here we show that transcriptionally active chromatin is preferentially repaired by HR. Using chromatin immunoprecipitation-sequencing (ChIP-seq), to analyse repair of multiple DSBs induced throughout the human genome, we identify an "HRprone" subset of DSBs that recruit the HR protein RAD51, undergo resection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

54
713
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 583 publications
(769 citation statements)
references
References 52 publications
54
713
1
1
Order By: Relevance
“…As previously reported in literature (Aymard et al, 2014), γH2AX ChIP-seq signal showed that, upon 4OHT induction, phosphorylation of histone H2AX established a megabaselarge zone of modified chromatin surrounding the AsiSI-DSB ( Figure 1A and B).…”
Section: Drosha Is Recruited To Dsbssupporting
confidence: 59%
See 4 more Smart Citations
“…As previously reported in literature (Aymard et al, 2014), γH2AX ChIP-seq signal showed that, upon 4OHT induction, phosphorylation of histone H2AX established a megabaselarge zone of modified chromatin surrounding the AsiSI-DSB ( Figure 1A and B).…”
Section: Drosha Is Recruited To Dsbssupporting
confidence: 59%
“…http://dx.doi.org/10.1101/261289 doi: bioRxiv preprint first posted online Feb. 7, 2018; near the DNA end, a localization which very much resembles that of NHEJ-repair factors such as XRCC4 (Aymard et al, 2014). Consistently, DROSHA accumulates preferentially at NHEJ-prone sites and its association with damaged chromatin is enhanced by NHEJ stimulation and HR suppression, as achieved by CtIP silencing.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations